Clinical impact of unclassified variants of the BRCA1 and BRCA2 genes. Issue 11 (1st October 2011) - Akbari, Mohammad R; Zhang, Shiyu; Fan, Isabel; Royer, Robert; Li, Song; Risch, Harvey; McLaughlin, John; Rosen, Barry; Sun, Ping; Narod, Steven A
Abstract : Women who carry a pathogenic mutation in BRCA1 or BRCA2 have high risks of developing breast and ovarian cancers. The functional effect of many missense variants on BRCA1 and BRCA2 protein function is not known. Here, the authors construct a historical cohort of 4030 female first-degree relatives of 1345 unselected patients with ovarian cancer who have been screened for BRCA1 and BRCA2 mutations. The authors compared the risks by the age of 80 years for all cancers combined in female first-degree relatives of women with a pathogenic mutation, women with a variant of unknown significance (unclassified variant) and non-carriers. The cumulative risk of cancer among the relatives of patients with a pathogenic mutation was much higher than the risk in relatives of non-carriers (50.2% vs 28.5%; HR=2.87, p<10 −4 ). In contrast, the cumulative risk of cancer among relatives of patients carrying an unclassified variant was similar to the risk of cancer for relatives of non-carriers (27.6% vs 28.5%; HR=1.08, p=0.79). The authors used three different algorithms to predict the pathogenicity of unclassified variants and compared their penetrance with non-carriers. In this sample, only Align Grantham Variation Grantham Deviation appeared to predict penetrance based on first-degree relatives.